No more teasing - Manushkin, Fran.; Lyon, Tammie (Minneapolis : Picture Window Books, 2010)
The class bully loves to tease Katie Woo until she decides to ignore him.
005-007.
RL: 2.8.
Guided reading level: H.
Keywords: Bullies -- Fiction; Teasing -- Fiction; School stories; Chinese Americans -- Fiction